Directed evolution of an amine transaminase for the synthesis of an Apremilast intermediate via kinetic resolution. (1st August 2021) - Xiang, Chao; Wu, Shuke; Bornscheuer, Uwe T.
Graphical abstract: Abstract: Apremilast is an important active pharmaceutical ingredient that relies on a resolution to produce the key chiral amine intermediate. To provide a new catalytic and enzymatic process for Apremilast, we performed the directed evolution of the amine transaminase from  Vibrio   fluvialis . Six rounds of evolution resulted in the VF-8M-E variant with > 400-fold increase specific activity over the wildtype enzyme. A homology model of VF-8M-E was built and a molecular docking study was performed to explain the increase in activity. The purified VF-8M-E was successfully applied to produce the key chiral amine intermediate in enantiopure form and 49% conversion via a kinetic resolution, representing a new enzymatic access towards Apremilast.